2019
DOI: 10.1039/c9cc00218a
|View full text |Cite
|
Sign up to set email alerts
|

Single-component molecular conductor [Pt(dmdt)2]—a three-dimensional ambient-pressure molecular Dirac electron system

Abstract: [Pt(dmdt)2], an air-stable single-component molecular conductor, contains massless Dirac electrons and carries Dirac nodal lines at ambient pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 32 publications
5
43
0
Order By: Relevance
“…In addition, we calculate the magnetic susceptibility. We show that the T -linear behavior of the magnetic susceptibility at a high temperature is consistent with the experimental result, 28) supporting the existence of Dirac nodal line. We argue that the depletion of the magnetic susceptibility observed experimentally at a low temperature 28) cannot be explained only by the effect of a realistic SOC.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, we calculate the magnetic susceptibility. We show that the T -linear behavior of the magnetic susceptibility at a high temperature is consistent with the experimental result, 28) supporting the existence of Dirac nodal line. We argue that the depletion of the magnetic susceptibility observed experimentally at a low temperature 28) cannot be explained only by the effect of a realistic SOC.…”
Section: Introductionsupporting
confidence: 88%
“…A characteristic of the energy band structure of [Pt(dmdt) 2 ] is the three isolated bands near the Fermi energy. 28) We construct the three-orbital tight-binding model focusing on these three isolated bands by Wannier fitting. Fig.…”
Section: Tight-binding Model Based On Wannier Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of its analogs, [Au(Et-thiazdt) 2 ] [7] and [Au(Et-thiazds) 2 ], which features S substituted by Se [8], showed that they turn metallic at 1.3 GPa and 0.6 GPa, respectively, values which compare favorably with the simple metal dithiolene complex, [Ni(dmit) 2 ], which becomes metallic at 15.9 GPa [9]. In single-component molecular conductors that meet certain conditions, the HOMO band and LUMO band can touch at a single point to form a Dirac electron system [10,11]. We have employed first-principles density functional theory (DFT) calculations to understand the single-component crystal [Pd(dddt) 2 ] (dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate), which exhibits temperature-independent resistivity at 12.6 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Indeed, after this discovery, the semimetal with open nodal lines has been found in another single-component molecular conductor [Pt(dmdt) 2 ] (dmdt = dimethyltetrathiafulvalenedithiolate). [16][17][18] Nodal-line semimetals where the conduction and valence bands touch each other along a line in the three-dimensional Brillouin zone have aroused broad interest in the possibility of topologically nontrivial states. [19][20][21][22][23][24][25][26][27][28] The crystal of metal dithiolene complex [Pd(dddt) 2 ] is an insulator at ambient pressure.…”
Section: Introductionmentioning
confidence: 99%